2014
DOI: 10.3171/2014.2.jns131288
|View full text |Cite
|
Sign up to set email alerts
|

Atrophic changes in the trigeminal nerves of patients with trigeminal neuralgia due to neurovascular compression and their association with the severity of compression and clinical outcomes

Abstract: S trong evidence suggests that in classic trigeminal neuralgia (TN) caused by neurovascular compression (NVC), the neuralgia is related to morphological and structural changes in the trigeminal nerve (TGN) that are probably the result of chronic vascular compression. Morphological changes in the nerve include nerve deviation, distortion, groove formation, and atrophy. 5 Atrophy of the nerve is seen in most cases of TN 20 and is probably attributable to structural abnormalities such as axonal loss and demyelina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
67
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 21 publications
(35 reference statements)
6
67
2
1
Order By: Relevance
“…Another recent study, by Leal and colleagues, evaluated 50 patients with unilateral idiopathic TN to determine if there is a relationship among the characteristics of symptoms, NVC, and clinical outcomes after MVD. 10 They demonstrated that greater atrophy at the trigeminal root entry zone was associated with more severe vascular compression and significantly better clinical outcome, which is consistent with our observation that atrophy in the proximal nerve near the root entry zone is associated with a trend toward better outcome. However, that study did not evaluate the nerve along its entire course but only measured the midcisternal segment.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Another recent study, by Leal and colleagues, evaluated 50 patients with unilateral idiopathic TN to determine if there is a relationship among the characteristics of symptoms, NVC, and clinical outcomes after MVD. 10 They demonstrated that greater atrophy at the trigeminal root entry zone was associated with more severe vascular compression and significantly better clinical outcome, which is consistent with our observation that atrophy in the proximal nerve near the root entry zone is associated with a trend toward better outcome. However, that study did not evaluate the nerve along its entire course but only measured the midcisternal segment.…”
Section: Discussionsupporting
confidence: 80%
“…Our data suggest that the story may be a bit more complex: Atrophy of the nerve in the cistern seems to be associated with better prognosis, possibly due to its correlation with vascular compression, but more distal atrophy (i.e., away from the site of vascular compression) might represent a poor prognosis, possibly due to intrinsic changes in the nerve. 10 As such, we have been able to distinguish 2 types of trigeminal nerve atrophy with different implications for outcome after MVD.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations